Grade level influence in middle school students' spatial‐scientific understandings of lunar phases. (10th April 2022) - Wilhelm, Jennifer; Cole, Merryn; Driessen, Emily; Ringl, Samantha; Hightower, Andromeda; Gonzalez‐Napoleoni, Javier; Jones, Jasemine
Abstract: This research with middle school students from Kentucky (KY) and Nevada (NV) provides a snapshot of students' spatial‐scientific understandings as we explored how well students understand lunar‐related content, both spatially and scientifically, after receiving instruction with similar curricular Earth‐Space content. Utilizing a lens of spatial reasoning ability, we further compared the ways middle level grade (sixth vs. eighth) factored into how well students comprehend the complexities of the Earth/Moon/Sun system and the cause of lunar phases. NV teaches Moon phases in eighth grade (age of 13–14) while KY teaches phases in sixth grade (age of 11–12). To be clear, we are not claiming that sixth graders and eighth graders are similar cognitively. Since phases are only taught formally once (at the middle level), we are exploring how well students understand these lunar‐related, spatial‐scientific concepts at the conclusion of their formal instruction. The majority of the states teach lunar phases either in sixth grade or in eighth grade; it is a state's choice. The rationale for this study is to begin the conversation regarding Does grade level matter on science content that requires spatial reasoning ability? This study will begin to shed light on this topic. The research questions specifically investigated for this study were: (1) How do sixth and eighth grade students compare in terms of their spatial ability and lunar knowledge as measured via content surveys? (2) How do sixth and eighth grade students compare in their spatial awareness and description of the Earth/Moon/Sun system as measured via clinical interviews? (3) How do quantitative and qualitative datasets compare/contrast with each other to create a complex snapshot of sixth graders versus eighth graders spatial‐scientific understandings of the Moon and its phases?